Hunting for ecological indicators: are large herbivore skeleton measures from harvest data useful proxies for monitoring? - Pedersen, Åshild Ønvik; Bårdsen, Bård-Jørgen; Veiberg, Vebjørn; Irvine, Justin R; Hansen, Brage Bremset (European Journal of Wildlife Research, 2023)
Hunter-collected data and samples are used as indices of population performance, and monitoring programs often take advantage of such data as ecological indicators. Here, we establish the relationships between measures of skeleton size (lower jawbone length and hind-leg length) and autumn carcass mass of slaughtered individuals of known age and sex of the high Arctic and endemic Svalbard reindeer (Rangifer tarandus platyrhynchus). We assess these relationships using a long-term monitoring dataset derived from hunted or culled reindeer. The two skeleton measures were generally strongly correlated within age class. Both jaw length (R2 = 0.78) and hind-leg length (R2 = 0.74) represented good proxies of carcass mass. These relationships were primarily due to an age effect (i.e. due to growth) as the skeleton measures reached an asymptotic size at 4–6 years of age. Accordingly, strong positive correlations between skeleton measures and carcass mass were mainly evident at the young age classes (range r [0.45–0.84] for calves and yearlings). For the adults, these relationships weakened due to skeletal growth ceasing in mature animals causing increased variance in mass with age—potentially due to the expected substantial impacts of annual environmental fluctuations. As proxies for carcass mass, skeleton measurements should therefore be limited to young individuals. Although body mass is the ‘gold standard’ in monitoring large herbivores, our results indicate that skeleton measures collected by hunters only provide similar valuable information for young age classes, particularly calves and yearlings. In sum, jaw length and hind-leg length function as proxies identical to body mass when documenting the impacts of changing environmental conditions on important state variables for reindeer and other herbivores inhabiting highly variable environments. Arctic · Citizen science · Hunter-collected data · Life history · Terrestrial large herbivore Hunting for ecological indicators: are large herbivore skeleton measures from ...